Przecena jako instrument aktywizacji sprzedaży - Kałek, Bożena B. (Wydział Prawa i Administracji UAM, 1972)
After the price reduction system had been adhered to in our country for several years, some shortcomings of the organization and the scheme of the price reduction as well as of the bargain sales became obvious. There are some doubts about the justification of creating funds for price reduction and commercial risks. Repricing does not take place only in Poland. Other countries also apply various systems of building up reserves to finance the effects of reduced prices as well as various mean of stimulating demand. The aim of this paper is to consider how to take advantage of the wide experience of the trade abroad to increase the effectiveness of the Polish repricing system. The first part of the paper deals with principles of price reduction in the socialist countries where in spite of similar forms of governing the repricing systems differ considerably. Principles of creating and using the repricing funds in Poland, the German Democratic Republic, Hungary, Bulgaria, Rumania and Czechoslovakia are presented in that part. In order to give a picture how repricing is carried out in different market conditions the experiences of the Jugoslavian and Swedish trade are shown. In the second part of the paper an analysis is made, aiming at an improvement of the Polish system of price reduction and taking into account foreign solutions. The application of some of them might rise the efficiency of our price reductions and ensure better economic effects of our commercial enterprises.
Price Reduction as a Means of Sale Activation